Interleukin-6 Promotes Epithelial-Mesenchymal Transition and Cell Invasion through Integrin β6 Upregulation in Colorectal Cancer. (13th August 2020) - Sun, Qi; Shang, Yukui; Sun, Fengkai; Dong, Xiwen; Niu, Jun; Li, Fanni
Abstract : The metastatic potential of colorectal cancer (CRC) is intensively promoted by the tumor microenvironment (TME) in a paracrine manner. As a pleiotropic inflammatory cytokine, Interleukin-6 (IL-6) is produced and involved in CRC, the same scenario where integrin α v β 6 also becomes upregulated. However, the relationship between IL-6 and integrin α v β 6 as well as their involvement in the crosstalk between CRC and TME remains largely unclear. In the present study, we demonstrated a positive correlation between the expression of IL-6 and integrin β 6 in CRC samples. The mutually promotive interaction between CRC and TME was further determined by an indirect coculture system. CRC cells could augment the secretion of IL-6 from fibroblasts, which in return induced invasion and integrin β 6 expression of CRC cells. Through the classic IL-6 receptor/STAT-3 signaling pathway, IL-6 mediated the upregulation of integrin β 6, which was involved in the invasion and epithelial-mesenchymal transition of CRC cells induced by IL-6. Taken together, our results reveal a paracrine crosstalk between IL-6 signals originating from the TME and increased the integrin β 6 level of CRC. IL-6 induces CRC invasion via upregulation of integrin β 6 through the IL-6 receptor/STAT-3 signaling pathway. Combined inhibition of IL-6 along with integrin β 6-targeted strategy may indicate new directions for antitumor strategies for CRC.